GENERALIZED MIXED GENERAL VECTOR VARIATIONAL-LIKE INEQUALITIES IN TOPOLOGICAL VECTOR SPACES - Ding, X. P.; Salahuddin, - (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In this work, we consider and study new kinds of generalized mixed general vector variational-like inequalities in real topological vector spaces. We use the Ferro minimax theorem to discuss the existence of weak and strong solutions for the generalized mixed general vector variational-like inequality problems.